2017
DOI: 10.4093/dmj.2017.41.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lobeglitazone, a Novel Thiazolidinedione, on Bone Mineral Density in Patients with Type 2 Diabetes Mellitus over 52 Weeks

Abstract: BackgroundThe aim of this multicenter, randomized, double-blind study was to examine the effect of lobeglitazone, a novel thiazolidinedione, on the changes in bone mineral density (BMD) in patients with type 2 diabetes mellitus.MethodsA 24-week, double-blinded phase was followed by a 28-week, open-label phase, in which the placebo group also started to receive lobeglitazone. A total of 170 patients aged 34 to 76 years were randomly assigned in a 2:1 ratio to receive lobeglitazone 0.5 mg or a matching placebo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Additionally, these drugs have restricted prescription or have been withdrawn from the market due to the adverse effects, including weight gain, liver injury, increased risk of bone fracture, and heart failure . However, the discovery of and research on PPARγ agonists have continued, and some of these agonists have demonstrated safe use . In this study, morin was identified as a potential agonist for PPARγ.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, these drugs have restricted prescription or have been withdrawn from the market due to the adverse effects, including weight gain, liver injury, increased risk of bone fracture, and heart failure . However, the discovery of and research on PPARγ agonists have continued, and some of these agonists have demonstrated safe use . In this study, morin was identified as a potential agonist for PPARγ.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the underlying mechanism by which thiazolidinediones may increase the risk of fracture did not appear to be explained by the effect of these medications on bone turnover markers . Notably, 52 weeks of treatment with 0.5 mg of lobeglitazone, a novel thiazolidinedione that has been approved in South Korea did not appear to have a negative effect on BMD in the femoral neck and total hip compared with the placebo . Limited evidence from RCTs has indicated that the negative effects of thiazolidinediones on bone may not worsen after the discontinuation of use, suggesting causality between these medications and bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the newer TZD, lobeglitazone, when compared with placebo over a 52‐week treatment period, was not associated with a significant decrease in BMD in 112 adults with T2D (mean age ~56 years; duration of T2D ~4 years); however, these relatively better skeletal outcomes need to be confirmed with further studies, as there are no long‐term data yet available.…”
Section: Drugs and Bonementioning
confidence: 96%